2018
DOI: 10.14236/ewic/hci2018.160
|View full text |Cite
|
Sign up to set email alerts
|

Design Patterns to Enhance Teens’ Museum Experiences

Abstract: Teenagers are an understudied group within the Interaction Design and Children community. Museums and cultural heritage spaces offer solutions for young children but do not target teenagers in particular. Teens, are a large pool of potential museum audiences. They should be given a "voice" and involved early in the design process to maximize chances of involvement in the museum practices and offers, hence, it is crucial to study their interests and desires to deploy a high quality and enjoyable product. For th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…In addition, previous studies have focused on the importance of creating programs in cultural institutions for one specific target group of visitors and developing approaches for their engagement. For example, those aimed at people with some kind of disability such as Alzheimer's disease or dementia (Camic et al, 2016;Rosenberg, 2009;Windle et al, 2018), ethnic minority groups (Le and Fujimoto, 2011), different age groups including children (Birch, 2018;Song et al, 2017;Eluyefa, 2017;Musacchio et al, 2015;Curtis and Chavez, 2013;Jung et al, 2018;Andre et al, 2017;Kalumpahaiti, 2018), teenagers and young adults (Ces ario et al, 2018;Lattarulo et al, 2017;Shrapnel, 2012;Fors, 2013;Tajt akov a and Arias-Aranda, 2008) and seniors (Traboulsi et al, 2018;Bernard and Rickett, 2017;Avellino, 2016). However, there are no studies that compare the compatibility of cultural offer with the needs of different age groups, noticed by Boži c et al (2018), where the authors propose more research on the cultural needs and preferences of different age groups of cultural visitors in Serbia.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, previous studies have focused on the importance of creating programs in cultural institutions for one specific target group of visitors and developing approaches for their engagement. For example, those aimed at people with some kind of disability such as Alzheimer's disease or dementia (Camic et al, 2016;Rosenberg, 2009;Windle et al, 2018), ethnic minority groups (Le and Fujimoto, 2011), different age groups including children (Birch, 2018;Song et al, 2017;Eluyefa, 2017;Musacchio et al, 2015;Curtis and Chavez, 2013;Jung et al, 2018;Andre et al, 2017;Kalumpahaiti, 2018), teenagers and young adults (Ces ario et al, 2018;Lattarulo et al, 2017;Shrapnel, 2012;Fors, 2013;Tajt akov a and Arias-Aranda, 2008) and seniors (Traboulsi et al, 2018;Bernard and Rickett, 2017;Avellino, 2016). However, there are no studies that compare the compatibility of cultural offer with the needs of different age groups, noticed by Boži c et al (2018), where the authors propose more research on the cultural needs and preferences of different age groups of cultural visitors in Serbia.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the co-design sessions (see [13,14,16]) suggested that teenagers particularly appreciate mobile experiences that include novel technologies, in particular Augmented Reality (AR) and Virtual Reality (VR); they are also keen to share their experiences via social media; they favor options for different tours to engage with different content; and suggest a mix of stories and games (they proposed games with treasure-hunts, competition, timeout and collection strategies; and stories that give the opportunity to become protagonists of the experience, engage directly with the exhibits and connect to it emotionally when possible). All these elements that emerged as important in the creative phase were taken into account in the design phase discussed next.…”
Section: Co-designing With Teenagersmentioning
confidence: 99%
“…According to formal studies about teenage preferences regarding museum engagement, Cesário et al [8,9] identified that teenage audiences particularly appreciate mobile experiences that include 1) Gaming and storytelling aspects, 2) Interaction elements, 3) Social media connections, and 4) Museum and exhibits relevant information. To contribute in filling in the gap regarding teenage engagement in museums, we designed the Memories of Carvalhal's Palace dual experience, geared towards better understanding teenagers' preferences and needs in museum contexts.…”
Section: Features On Enjoyable Museum Experiences For Teenagersmentioning
confidence: 99%